Adaptation for a Changing Environment: Developing learning and teaching with information and communication technologies - Kirkwood, Adrian; Price, Linda (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
This article examines the relationship between the use of information and communication technologies (ICT) and learning and teaching, particularly in distance education contexts. We argue that environmental changes (societal, educational, and technological) make it necessary to adapt systems and practices that are no longer appropriate. The need to adapt, however, can be perceived as being technology-led and primarily concerned with requiring academic staff to develop their skills in using ICT. We provide a critique of continuing professional development (CPD) for using ICT in teaching and learning that does not entail examining the impact of environmental changes upon the assumptions, goals, and strategies which underlie and shape an organisation’s educational practices. In particular, we oppose CPD that concentrates on the individual teacher and their use of ICT. Instead, we contend that professional development should focus upon the scholarship of teaching and learning, and must also reflect the wider organisational context within which ICT is managed and used.